TEMPERATURE VARIABILITY AT SENUNU BAY, WEST SUMBAWA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
The purposes of this study were to determine the variability of temperature and its relation to regional processes in the Senunu Bay. The result showed clear vertical stratifications i.e., mixed layer thickness about 39-119 m with isotherm of 27°C, thermocline layer thickness about 83-204 m with isotherm of 14–26°C, and  the deeper layer from the thermocline lower limit to the sea bottom with isotherm